Coronary artery disease with type 2 diabetes and other risk factors: A tertiary care hospital in Bangladesh - Khanam, Parvin Akter; Begum, Tanjima; Chowdhury, Abhijit; Habib, Samira Humaira (Bangladesh Critical Care Journal, 2019)
Background: The aim of this study was to determine the prevalence of coronary artery disease (CAD) and to identify the various risk factors related to this complication in subject with diabetes. Methods: The study was cross-sectional and conducted in out-patients department of BIRDEM, from July 2016 to December 2017. Subjects were considered at age 30 to 70 years and duration of diabetes was 5-10 years. Investigations included socio-demographic (age, sex, education etc.), anthropometry (height, weight) and blood pressure. Blood samples were collected for HbA1c, fasting blood glucose (FBG), 2 hour after breakfast (2HABF), lipid profile and CAD were taken from the record books which was diagnosed by respective physician. Results: A total of 221 type 2 diabetes mellitus (T2DM) patients data were taken from the record books. There were 38 patients who had developed CAD and the prevalence of CAD was 17.2%. The study found that it had no significant difference between gender and CAD. The study also found that advanced age (OR=2.16;p=<0.025), lack of physical exercise (OR=3.46; p=0.001), rural patients (OR=2.09; p=0.043), no schooling (OR=4.06; p=0.001), long duration of diabetes (OR=2.87;p=0.018), SBP(OR=2.99; p=0.003), DBP(OR=2.33; p=0.025) and increasing 2HABF (OR=2.6; p=0.026) were independent significant risk factors for CAD. Conclusions: The study concluded that the prevalence of CAD in Type 2 diabetes was more common and comparable to other developed countries. The study also proved that older age, rural community, lack of education, lack of physical exercise, long duration of diabetes, high blood pressure and high blood glucose were significantly independent risk factors for development of CAD. Therefore, the study concluded that lifestyle modification and tight blood pressure control with diabetes is key part to reduce CAD. Bangladesh Crit Care J March 2019; 7(1): 20-25